Effects of ported shroud casing treatment on the acoustic and flow behaviour of a centrifugal compressor. (August 2020) - Sharma, Sidharath; García-Tíscar, Jorge; Allport, John M; Barrans, Simon; Nickson, Ambrose K
Centrifugal turbomachines of smaller sizes operating at higher speeds have become pervasive due to the increased specific power and reliability achieved by improvements in manufacturing, materials and computational methods. The presence of these small turbomachines, specifically compressors, in helicopters, unmanned aerial vehicles, auxiliary power units, turbochargers and micro gas turbines necessitates superior aerodynamic performance over a broad operational range, which is widely achieved by ported shroud casing designs. In addition to aerodynamic performance, acoustic emissions have become a critical aspect of design for these small centrifugal compressors due to high operational speeds. Furthermore, the literature on the acoustic effects of the casing treatment is rather limited. Therefore, the impact of ported shroud casing treatment on the acoustic and flow features of the compressor operating at the design and near-surge conditions have been quantified by numerically modelling the open and blocked configuration of the compressors. Upon comparing with experimental results, the numerical spectra are shown to capture the differences between the two configurations at the investigated operating points with reasonable accuracy. Although the casing treatment is generally seen to decrease the overall acoustic emission of the compressor at both operating conditions, increased propagation of tonal content in the direction upstream to the impeller is observed, particularly for design operation. Broadband characteristics in the lower and medium frequency regions usually associated with near-surge operation including 'whoosh' noise are observed to be alleviated by the ported shroud casing treatment.